Pencarian Jadwal Kuliah Pengganti: OUTTER JOIN - Katon Wijana; Yetli Oslan; Harianto Kristanto (Fakultas Teknologi Informasi, 2023)
The class schedule is determined during student registration, but in practice, there is a possibility of schedule failure due to various reasons, such as a lecturer having other important commitments on that schedule, national holidays, or other reasons. According to academic regulations, the number of face-to-face class meetings has been predetermined, which is 14 meetings. Therefore, if a class meeting fails to take place, it must be replaced with a substitute schedule. Finding a substitute class schedule does not only consider the availability of the respective lecturer's schedule but also takes into account the availability of classrooms and the schedules of each student to ensure that all students can attend (not attending other courses). This way, the substitute schedule can be implemented without disrupting students' activities. Unlike previous research, which focused on generating class schedules using search and filtering techniques, this study will display all alternative substitute schedules that can be implemented without disturbing the schedules of lecturers, students, or room usage by utilizing multiple table queries with outer join relationships. Finding a substitute class schedule does not only consider the availability of the respective lecturer's schedule but also takes into account the availability of classrooms and the schedules of each student to ensure that all students can attend (not attending other courses). This way, the substitute schedule can be implemented without disrupting students' activities. Unlike previous research, which focused on generating class schedules using search and filtering techniques, this study will display all alternative substitute schedules that can be implemented without disturbing the schedules of lecturers, students, or room usage by utilizing multiple table queries with outer join relationships. Keywords-class schedule, substitute schedule, lecturer schedule, student schedule, room usage.